Application of TGT Type Cooperative Model With Kahoot to Improve Cognitive Learning Outcomes of Senior High School Students - Dwi Rahmayanti; Zulhelmi Zulhelmi; Romi Putra (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2024)
This research aims to determine the increase in student learning gains by implementing the TGT-type cooperative model through Kahoot media on mechanical wave material in class XI SMA N 2 Singingi. The research uses Quasi-Experimental Design type of research with a